Peran Guru dalam implementasi sistem among pada pembelajaran PPKn Kelas IV SD Negeri Kanggotan Pleret Bantul - Orbiyanto, Thomas Leo; Chairiyah; Nugroho, Irfan Adi (Journal of Contemporary Issues in Primary Education, 2023)
The Teacher's Role in the Implementation of the Among System in Class IV PPKn Learning at SD Negeri Kmember Pleret Bantul. Thesis of the Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Tamansiswa University, Yogyakarta.The purpose of this study was to describe the teacher's role in the implementation of the among system in the fourth grade PPKn SD Negeri Pleret Bantul. To find out the supporting and inhibiting factors of the teacher's role in the implementation of the among system in class IV PPKn SD Negeri Pleret Bantul. To find out the impact of the teacher's role in the implementation of the among system in class IV PPKn learning at SD Negeri Kmember Pleret Bantul. This research was conducted at Kmember Pleret Public Elementary School, Bantul. This research was conducted in February 2023. The subjects in this study were school principals, grade IV teachers and grade IV students. This data collection technique uses observation techniques, interviews and documentation. The research instrument is an observation guide, interview guide and documentation guide. Test the validity of the data using source triangulation and technical triangulation and using reference materials. Data analysis techniques in this study used Miles and Huberman's analysis which consisted of data collection, data reduction, data presentation and data withdrawal. The results of the study show that (1) the role of the teacher in implementing the among system in Civics learning is very important, namely the teacher as a teacher or educator, the teacher as a guide, the teacher as a mediator and facilitator, the teacher as an evaluator, the teacher as an example and a good role model, and being able to protect , provide direction, encouragement or motivation and realize the independent spirit of students in learning according to the interests and talents of students. (2) Factors supporting the teacher's role in implementing the among system are the competence or ability of the teacher in teaching, the teacher's understanding of the among system, the teacher's personality or level of concern for students, the parents' trust in the teacher and the support from the school principal. (3) The inhibiting factors include the level of care and patience in educating students, the limited time used and the child's willingness to learn. (4) The impact is that learning objectives will be successfully achieved, student character can develop optimally, students can feel comfortable in learning activities in the school environment, students will feel more enthusiastic about learning and feel happy in participating in learning activities so that the School Movement is Fun (GSM) can be achieved well.